Pengaruh Kepemimpinan Transformasional Dan Budaya Organisasi Terhadap Kepuasan Kerja Dan Kinerja Karyawan PT. Jamsostek (Persero) Cabang Surabaya - Ritawati, Agustina (Program Doktor Ilmu Ekonomi, 2013)
Research objectives to be achieved from this study are to analyze and prove: Transformational leadership influence on job satisfaction of employees of PT. Jam-sostek (Persero) Branch Surabaya. Organizational culture influence on job satisfaction of employees of PT. Jamsostek (Persero) Branch Surabaya. Transformational leadership influence on the performance of employees of PT. Jamsostek (Persero) Branch Surabaya. Organizational culture influence on employee performance PT. Jamsostek (Persero) Branch Surabaya. Job satisfaction influence on the performance of employees of PT. Jamsostek (Persero) Branch Surabaya.The study subjects taken as many as 111 people, this number is expected to have a minimum number of eligible study sample. Data analysis technique used is to use the software SPSS and AMOS-SEM.The results showed that: Transformational leadership has a positive and significant influence on job satisfaction. Organizational culture has a significant and positive influence on job satisfaction.Transformational leadership has a positive and significant impact on employee performance . Organizational culture has a significant and positive impact on employee performance. Job satisfaction has a positive and significant impact on employee performanceKey Words : Transformational Leadership, Organizational Culture, Job Satisfaction and Employee Performance